Optimizing the Utilization of Online Business Licensing to Accelerate Business Licensing Services for Micro Businesses - Rahayu, Sang Ayu Putu; Puteri, Dina Silvia (Jurnal Abdimas, 2025)
Micro business owners need legal permits, such as a Business Identification Number (NIB), which can be obtained through the OSS RBA (Online Single Submission Risk-Based Approach) system. However, many lack awareness of its importance and accessibility. To address this, a community service program in Kebojongan Village aims to educate and assist local entrepreneurs in using OSS, simplifying business licensing, and supporting economic growth. With an NIB, micro businesses can obtain additional permits like legal certification, Indonesian National Standards (SNI), and Halal Product Guarantee Certificates. The program includes interviews, counseling, mentoring, and evaluations on OSS RBA and NIB registration. Challenges faced include forgotten account passwords and cases where a National Identity Number (NIK) was registered by someone else, restricting access. This initiative is expected to accelerate business licensing for micro businesses in Kebojongan Village, fostering their development and sustainability.